Pengaruh Persepi Mahasiswa Tentang Peluang Kerja Dan Status Sosial Ekonomi Orang Tua Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Akuntansi Universitas Muhammadiyah SurakartaAngkatan 2012 - Nur Hidayati, Anis Farida; , Drs. Muhammad Yahya, M.Si (2017)
The purposes of this research are: 1) to determine the influence of students' perceptions on employment opportunities to the student's interest in entrepreneurship. 2) To determine the influence of socio-economic status of parents to the student's interest in entrepreneurship. 3) To determine the influence of students' perceptions on employment opportunities and socio-economic status of parents to the student's interest in entrepreneurship. This research includes in quantitative research which used a statistical methods to derive the conclusion. The population in this reserach was all students of accounting education of 2012. The sample was taken from 105 students with proportional random sampling. Necessary data obtained through questionnaires and documentation. Before being tested, the questionnaire validity and reliability were previously tested. Data analysis technique used in this research is multiple linear regression analysis, t-test, F-test, and the relative contribution and effective. The results of the regression analysis obtained regression equation of: Y = 5.657 + 0, 410 X1 + 0, 740 X2. The equation shows that the interest in entrepreneurship is influenced by the perception of students on employment opportunities and socio-economic status of parents. The conclusions drawn were: 1) The perception of students on employment opportunities to the interest in entrepreneurship can be accepted. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 6.434> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 39% and the effective contribution of 24.3%. 2) Socio-economic status of parents to the interest in entrepreneurship can be accepted. This is based on the multiple linear regression analysis (t test) note that tcount> ttable, is 8.874> 2.000 and the significance value <0.05, is 0.013 with relative contributions of 61% and 28% effective contribution. 3) Perception of students on employment opportunities and socio-economic status of parents to the interest in entrepreneurship can be accepted. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, is 102.140> 3.150 and the significance value <0.05, is 0.000. 4) The coefficient of determination (R2) of 0.623 indicates that the influence of students' perceptions on employment opportunities and socio-economic status of parents to the interest in entrepreneurship is 62.3%, while the rest influenced by other variables. Keywords: employment opportunities, socio-economic status of parents, and interest in entrepreneurship.